The influence of hormones on the lipid profile in the fat body of insects - M Cerkowniak; A Ostachowska; M Słocińska; G Rosiński; P Stepnowski; M Gołębiowski (Invertebrate Survival Journal, 2015)
Peptide hormones play a special role in the neuroendocrine systems of insects and affect a number of physiological processes related to their development, reproduction and behavior. The lipid content in the fat body of insects is closely correlated with the work of the endocrine glands. The lipid profile of the fat body of the Zophobas atratus beetle reveals a predominant proportion of triacylglycerols when compared to free fatty acids and other lipid compounds, such as fatty acid esters, fatty alcohols and sterols. Although it may depend on the stage of the insects’ development, the disparate impacts of the adipokinetic hormone (AKH) on the lipid content in the fat bodies of the feeding larvae and the non-feeding pupae of Z. atratus, may signify the different roles this hormone plays in the indirect control of the insects’ metabolism.